The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2337/dc06-0287
|View full text |Cite
|
Sign up to set email alerts
|

Normotensive Women With Type 2 Diabetes and Microalbuminuria Are at High Risk for Macrovascular Disease

Abstract: OBJECTIVE -The excess risk of macrovascular disease and death associated with diabetes seems higher in women than in men. The pathogenesis for this risk difference has not been fully elucidated. We investigated whether female sex was associated with macrovascular disease and death, independently of known risk factors related to type 2 diabetes, nephropathy, or retinopathy in normotensive patients with type 2 diabetes and microalbuminuria.RESEARCH DESIGN AND METHODS -We conducted a prospective, prolonged follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This risk was 3.19 times higher in women in unadjusted analysis and, after adjusting for established CVD risk factors (such as age, systolic BP, BMI, total-to-HDL cholesterol (HDLC) ratio, smoking and urinary albumin excretion or retinopathy), it was still increased to over twofold. Nevertheless, the limitations of this study were that it included a relatively small number of patients (46 men and 21 women) and it was confined to normotensive patients with microalbuminuria (26). Studies reporting an absolute risk of CVD death in diabetic sexes (most of them adjusted for CVD risk factors) are summarised in Table 3.…”
Section: Introductionmentioning
confidence: 99%
“…This risk was 3.19 times higher in women in unadjusted analysis and, after adjusting for established CVD risk factors (such as age, systolic BP, BMI, total-to-HDL cholesterol (HDLC) ratio, smoking and urinary albumin excretion or retinopathy), it was still increased to over twofold. Nevertheless, the limitations of this study were that it included a relatively small number of patients (46 men and 21 women) and it was confined to normotensive patients with microalbuminuria (26). Studies reporting an absolute risk of CVD death in diabetic sexes (most of them adjusted for CVD risk factors) are summarised in Table 3.…”
Section: Introductionmentioning
confidence: 99%
“…Heart disease remains the leading cause of mortality in people with diabetes. Previous research has shown that women with diabetes may be at higher risk for developing cardiovascular disease [27,28] than men and that mortality from both coronary heart disease [29,30] and stroke [31] is also higher in women with diabetes than men. While mortality was not assessed, our study did provide further evidence of higher odds of women having hypertension and yet, less likely to have heart disease than men with diabetes, a finding consistent in the literature [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have looked at differences in diabetes complications and diabetes management among men and women. For examples, studies have shown that the relative risk of cardiovascular disease (CVD), coronary artery disease and stroke is higher among women with diabetes than among men with diabetes [9][10][11][12][13][14][15]. Another study showed that women with diabetes may not reach the recommended therapeutic targets for lipid profile, blood pressure (BP) levels and Hemoglobin A1C (A1C), a measure of glycemic control, as a result of less aggressive management of diabetes compared to men with diabetes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that women with diabetes may be at higher risk for developing cardiovascular disease [27,28] than men and that mortality from both coronary heart disease [29,30] and stroke [31] is also higher in women with diabetes than men. While mortality was not assessed, our study did provide further evidence of higher odds of women having hypertension and yet, less likely to have heart disease than men with diabetes, a finding consistent in the literature [32,33].…”
Section: Discussionmentioning
confidence: 99%